Phosphorylation of Dynamin-Related Protein 1 (DRP1) Regulates Mitochondrial Dynamics and Skeletal Muscle Wasting in Cancer Cachexia - Mao, Xiangyu; Gu, Yihua; Sui, Xiangyu; Shen, Lei; Han, Jun; Wang, Haiyu; Xi, Qiulei; Zhuang, Qiulin; Meng, Qingyang; Wu, Guohao (Frontiers in Cell and Developmental Biology, 2021)
Background Cancer-associated cachexia (CAC) is a syndrome characterized by skeletal muscle atrophy, and the underlying mechanisms are still unclear. Recent research studies have shed light on a noteworthy link between mitochondrial dynamics and muscle physiology. In the present study, we investigate the role of dynamin-related protein 1 (DRP1), a pivotal factor of mitochondrial dynamics, in myotube atrophy during cancer-associated cachexia. Methods Seventy-six surgical patients, including gastrointestinal tumor and benign disease, were enrolled in the study and divided to three groups: control, non-cachexia, and cancer-associated cachexia. Demographic data were collected. Their rectus abdominis samples were acquired intraoperatively. Muscle fiber size, markers of ubiquitin proteasome system (UPS), mitochondrial ultrastructure, and markers of mitochondrial function and dynamics were assayed. A cachexia model in vitro was established via coculturing a C2C12 myotube with media from C26 colon cancer cells. A specific DRP1 inhibitor, Mdivi-1, and a lentivirus of DRP1 knockdown/overexpression were used to regulate the expression of DRP1. Muscle diameter, mitochondrial morphology, mass, reactive oxygen species (ROS), membrane potential, and markers of UPS, mitochondrial function, and dynamics were determined. Results Patients of cachexia suffered from a conspicuous worsened nutrition status and muscle loss compared to patients of other groups. Severe mitochondrial swelling and enlarged area were observed, and partial alterations in mitochondrial function were found in muscle. Analysis of mitochondrial dynamics indicated an upregulation of phosphorylated DRP1 at the ser616 site. In vitro, cancer media resulted in the atrophy of myotube. This was accompanied with a prominent unbalance of mitochondrial dynamics, as well as enhanced mitochondrial ROS and decreased mitochondrial function and membrane potential. However, certain concentrations of Mdivi-1 and DRP1 knockdown rebalanced the mitochondrial dynamics, mitigating this negative phenotype caused by cachexia. Moreover, overexpression of DRP1 aggravated these phenomena. Conclusion In clinical patients, cachexia induces abnormal mitochondrial changes and possible fission activation for the atrophied muscle. Our cachexia model in vitro further demonstrates that unbalanced mitochondrial dynamics contributes to this atrophy and mitochondrial impairment, and rebuilding the balance by regulating of DRP1 could ameliorate these alterations.